The scientific basis for the use of biomaterials in stress urinary incontinence (SUI) and pelvic organ prolapse (POP) - Colaco, Marc; Mettu, Jayadev; Badlani, Gopal (BJU international, 2015)
Objectives To review the scientific and clinical literature to assess the basis for the use of biomaterials in stress urinary incontinence (SUI) and pelvic organ prolapse (POP). Pelvic floor diseases (PFDS), such as SUI and POP, are common and vexing disorders. While synthetic mesh‐based repairs have long been considered an option for PFD treatment, and their efficacy established in randomised clinical trials, safety of its use has recently been called into question. Materials and Methods Using the PubMed, MEDLINE and Medical Subject Headings (MeSH) databases, we performed a critical review of English‐language publications that contained the following keywords: ‘pelvic organ prolapse’, ‘stress urinary incontinence’, ‘mesh’, ‘biomaterial’, ‘collagen’, ‘elastin’ and ‘extracellular matrix’. After reviewing for relevance for mesh use in the pelvis by two independent reviewers with a third available in the case of disagreement, a total of 60 articles were included in the present review. Results We found that many of the potential causes of PFDs are due to altered metabolism of patient extracellular matrix (specifically collagen, elastin, and their respective enzymes) and as such, repairs using native tissue may suffer from the same abnormalities leading to a subsequent lack of repair integrity. However, mesh use is not without its unique risks. Several publications have suggested that biomaterials may undergo alteration after implantation, but these findings have not been demonstrated in the normal milieu. Conclusion While the decision for the use of synthetic mesh is scientifically sound, its benefits and risks must be discussed with the patient in an informed decision‐making process.